Quasi-unsteady CHP Operation of Power Plants Thermal and Economic Effectiveness - Buryn, Zbigniew (Power Systems, 2016)
This book analyzes the continuous operation of a power plant with condensing power units in combined heat and power mode (CHP-mode) over a period of one year. Focusing on the operation of one and two power-unit systems with differing heat exchanger configurations, this book uses mathematical modeling of the steam-water cycle of a 370 MW power unit to calculate the operating characteristics and mass-energy balance of the system. Featuring comprehensive thermodynamic analysis of the quasi-unsteady operation of power units in cogeneration for electrical power generation, as determined by the Polish Power System, this work also includes an economic analysis of the power plant, presenting the costs and economic effectiveness of such a system.